SENSOR ERROR DETECTION SYSTEM ON AUTOMATIC WEATHER STATION USING LONG SHORT-TERM MEMORY ALGORITHM - Santoso, Bayu
The weather information in Indonesia plays a crucial role in various sectors due to the country's diverse weather and extreme climate phenomena. In aviation transportation, weather information helps determine new routes or avoid routes with adverse weather conditions, ensuring accurate flight path planning. The Meteorology, Climatology, and Geophysics Agency (BMKG) have the responsibility to disseminate weather information to the public. Currently, BMKG operates 124 Technical Implementation Units (UPT) meteorological stations observing and providing weather information across provinces in Indonesia. Of these, 62 UPT meteorological stations conduct automatic weather observations, while the rest still rely on manual observations.